Mitigation of single-phase voltage sag and swell with zigzag transformer - Basu, K. P.; Hafidz, S. A. (2008)
Voltage sag or swell in one phase of a 3-phase system due to LG fault, capacitor switching or any other reason is to be mitigated immediately for proper functioning of all the equipments. A 3-phase zigzag-winding transformer connected across a 3-phase star-connected load may mitigate the voltage sag or swell at any one phase of the load. The phase experiencing the voltage disturbance is disconnected from the source of supply first, while the other two phases remain connected to the source. The zigzag transformer immediately rebuilds the voltage across the load of the open phase and allows the current to flow to the open phase load. Very low value of zero sequence impedance of the zigzag transformer produces very small voltage drop and the open phase voltage nearly equals the normal voltage. After the disturbance disappears, the open phase of the transformer and load is reconnected to the supply.